Marketing of horticultural products in Muzaffarpur district of Bihar: Challenges and Opportunities for Marketing Horticultural Products in Muzaffarpur, Bihar (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Bihar is mainly an agricultural state with a large proportion of the population deriving theirlivelihoods from agriculture directly or indirectly. As the yields from agriculture tended to stagnate, amove towards diversification in agriculture through activities like horticulture, pisciculture, apiculture,dairy farming etc became necessary. Over the last few years, Bihar has emerged as a leader inhorticultural farming. Muzaffarpur has emerged as the hub of horticultural production. The articleexamines the issues pertaining to marketing of horticultural products in Muzaffarpur district usingprimary as well as secondary data.